Receptor tyrosine kinase signaling and targeted therapies - Wendt, Michael (Henry Stewart Talks, 2022)
Kinase signaling, HER2 amplification and overexpression in cancer, Therapeutic antibodies, Antibody-drug conjugates, Activation of EGFR by somatic mutation, Kinase inhibitors, MAPK-ERK pathway